Resilience in major Australian cities: assessing capacity and preparedness to respond to extreme weather events. Issue 4 (4th July 2018) - Horne, James
Abstract: The article examines the resilience of major Australian cities to extreme weather events. It reviews how and how well six of the largest Australian cities have responded to some recent water-related crises, covering droughts, floods and extreme storm events. It discusses examples of the preparedness for specific events, the immediate reaction to the event, the policy responses, and some of the more important challenges that remain.